Tailoring the radiotherapy approach in patients with anal squamous cell carcinoma based on inguinal sentinel lymph node biopsy. Issue 1 (22nd September 2020) - De Nardi, Paola; Mistrangelo, Massimiliano; Burtulo, Giovanni; Passoni, Paolo; Slim, Najla; Ronzoni, Monica; Canevari, Carla; Parolini, Danilo; Massimino, Luca; Franco, Pierfrancesco; Cassoni, Paola; Lesca, Adriana; et al.
Abstract: Background and Objectives: The aim of our study was to analyze the results of selective inguinal node irradiation in patients with anal cancer, based on the biopsy of the inguinal sentinel lymph node (SLN), in terms of local control and prognosis. Methods: Records of patients with anal squamous cell carcinoma from January 2001 to December 2016 were retrospectively reviewed. Tc99 lymphoscintigraphy was performed in all the clinically inguinal negative patients, followed by radio‐guided surgical removal of the inguinal SLN. All patients were treated with combined radiochemotherapy. In patients with negative sentinel nodes, the inguinal area was excluded in the radiotherapy field. Results: A total of 123 patients, 76 females (61.8%), mean age 60.1 ± 12.19 years old, underwent intraoperative lymph node retrieval. The histological analysis showed metastasis in the SLN in 28 patients (22.8%). The mean follow‐up was 43.44 ± 31.86 months. No inguinal recurrence was observed in patients with negative inguinal sentinel node(s). A statistically significant difference was observed for overall and disease‐free survivals in a patient with positive and negative inguinal sentinel nodes. Conclusions: In patients with anal canal cancer, the exclusion of the inguinal regions from the radiotherapy field, in patients with negative SLN, does not compromise locoregional control nor prognosis.